ANALISIS METODE PEMBELAJARAN ILMU NAḤWU PADA MAJELIS TAKLIM AL-AMANAH KEBON JERUK JAKARTA BARAT - Syarif, Fajar (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This article will discuss the learning method of Nahwu at Majelis Taklim al Amanah. It shows a method that is applied by KH. Muhammad Zein in Nahwu  learning by combining some methods in Nahwu learning. Poligamy that is applied by KH. Muhammad Zein can help students to get the language skill.  The writer has chosen this object research at Majelis Taklim al Amanah due to it uses Nahwu as a prime lesson and obligatory material for students, so the Nahwu position is so important and it is intensively learned. For the sources of this  research are from collaboration of library research and field research. It uses etnografy method (descriptive qualitative research) which focuses on Nahwu learning process at the Majlis Taklim. Learning with the poligamy system is a role model of learning for other educational institutions, so the learning purpose of Nahwu can be reached.